Epidemiology of injuries in National Collegiate Athletic Association men's wrestling: 2014-2015 through 2018-2019 - Powell, J. R.; Boltz, A. J.; Robison, H. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The first men's wrestling National Collegiate Athletic Association (NCAA) Championship was sponsored in 1928; since then, participation has increased. Background: Continued study of wrestling injury data is essential to identify areas for intervention based on emerging trends. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios (IRRs) were used to examine differential injury rates. Results: The overall injury rate was 8.82 per 1000 athlete exposures. The competition injury rate was significantly higher than practice injury rate (IRR = 4.11; 95% CI = 3.72, 4.55). The most commonly injured body parts were the knee (21.4%), shoulder (13.4%), and head/face (13.3%), and the most prevalently reported specific injury was concussion. Summary: These findings provide the most current update to injury incidence and outcomes in NCAA men's wrestling. We identify notable trends that warrant consideration in future research.